Seaweed composition from Bintulu coast of Sarawak, Malaysia - Zawawi, Mohd Hafizbillah; Idris, Mohd Hanafi; Mustafa Kamal, Abu Hena; King, Wong Sing (Asian Network for Scientific Information, 2014)
Species composition of seaweed and distribution were investigated in the coastal waters of Bintulu, Sarawak. The seaweed samples were collected during low tide between May 2011 and May 2012 from the six different stations. In total 54 species of seaweeds were identified from study areas of Bintulu coastal waters. Among them, 23 species were from Rhodophyta with 11 families, 15 species were from Phaeophyta with 2 families and 16 species were from Chlorophyta with 10 families. Seventeen species of seaweeds were recorded from the Tanjung Batu, while 23 species from Pantai Telekom, 14 species from Golden Beach, 26 species from Kuala Similajau, 12 species from Kuala Nyalau and 21 species from Batu Mandi. Seaweeds abundance was high in rocky substrate and Rhodophyta (11 families and 23 species) was the common and highest group of seaweeds in this coastal areas. Present study recorded high diversified seaweed species at the rocky shore area compare to reef area.